Representações sociais de meio ambiente e balneabilidade: Um estudo no Balneário do Açude, em Santa Rita – PB - Dautro, Grazziany Moreira (2018)
The Social Representations (RS) are common sense knowledge, created daily, in the conversations, under the influence of the communicative and interactive processes by people who play the role of social actors. The study of RS in environmental education, for example, has aroused interest in the scientific community because it has been a way of understanding the behavior of individuals in relation to the environment. In this sense, the present research had as objective to know the social representations and perception about the environment expressed by the residents, passers - by and frequenters of the Balneário do Açude - Santa Rita (PB - Brazil). Social representations were captured through a semi-structured interview with 17 questions, including the technique of free word evocations, about the profile of interviewes, environmental perception and multiple uses. The analysis of the data obtained was done using the software IRAMUTEQ as well as the technique of content analysis, proposed by Bardin (2016), used here to create the categories of environmental perception (naturalistic, sanitarian, sustainable, affepctive, manager) based on the semantic criterion. It was also analyzed the balneability of the site as information support for the research, using as parameters thermotolerant coliform from the filter membrane technique according to Standard Methods 922 d. As a social counterpart, an educational booklet was developed, containing information about the research and tips of local environmental conservation, conceived with the intention of contributing, lucidly, with the place studied, through the presentation of the results obtained in the research. The results indicated that social representations of the environment are formed by nature, its resources, and a concern with the cleanliness and preservation of the environment, a fact confirmed by the apprehension of environmental perception. Regarding the balneabilidad, it was verified that the waters of the Balneário do Açude are unsuitable for bathing in the dry period as in the rainy period. In spite of the results of improper bathing in Açude, it is important to note the finding of a coherence between the SRs captured and the concduct and behaviors of these actors in favor of environmental conservation.